The Effects of Fortetropin Supplementation on Body Composition, Strength, and Power in Humans and Mechanism of Action in a Rodent Model. (16th November 2016) - Sharp, Matthew H.; Lowery, Ryan P.; Mobley, C. Brooks; Fox, Carlton D.; de Souza, Eduardo O.; Shields, Kevin A.; Healy, James C.; Arick, Ned Q.; Thompson, Richard M.; Roberts, Michael D.; Wilson, Jacob M.
Abstract : Objective : The purpose of this study was to investigate the effects of Fortetropin on skeletal muscle growth and strength in resistance-trained individuals and to investigate the anabolic and catabolic signaling effects using human and rodent models. Methods : In the rodent model, male Wistar rats (250 g) were gavage fed with either 1.2 ml of tap water control (CTL) or 0.26 g Fortetropin for 8 days. Then rats participated in a unilateral plantarflexion exercise bout. Nonexercised and exercised limbs were harvested at 180 minutes following and analyzed for gene and protein expression relative to mammalian target of rapamycin (mTOR) and ubiquitin signaling. For the human model, 45 (of whom 37 completed the study), resistance-trained college-aged males were divided equally into 3 groups receiving a placebo macronutrient matched control, 6.6 or 19.8 g of Fortetropin supplementation during 12 weeks of resistance training. Lean mass, muscle thickness, and lower and upper body strength were measured before and after 12 weeks of training. Results : The human study results indicated a Group × Time effect ( p ≤ 0.05) for lean mass in which the 6.6 g (+1.7 kg) and 19.8 g (+1.68 kg) but not placebo (+0.6 kg) groups increased lean mass. Similarly, there was a Group × Time effect for muscle thickness ( p ≤ 0.05), which increased in the experimental groups only. All groups increased equally in bench press and leg press strength. In the rodent model, a main effect for exercise ( p ≤ 0.05) in which the control plus exercise but not Fortetropin plus exercise increased both ubiquitin monomer protein expression and polyubiquitination. mTOR signaling was elevated to a greater extent in the Fortetropin exercising conditions as indicated by greater phosphorylation status of 4EBP1, rp6, and p70S6K for both exercising conditions. Conclusions : Fortetropin supplementation increases lean body mass (LBM) and decreases markers of protein breakdown while simultaneously increasing mTOR signaling.